Optimal Control of a Fed-Batch Fermentation Involving Multiple Feeds - Chongyang Liu; Zhaohua Gong; Zhaoyi Huo; Bangyu Shen (Journal of Applied Mathematics, 2012)
A nonlinear dynamical system, in which the feed rates of glycerol and alkali are taken as the control functions, is first proposed to formulate the fed-batch culture of 1,3-propanediol (1,3-PD) production. To maximize the 1,3-PD concentration at the terminal time, a constrained optimal control model is then presented. A solution approach is developed to seek the optimal feed rates based on control vector parametrization method and improved differential evolution algorithm. The proposed methodology yielded an increase by 32.17% of 1,3-PD concentration at the terminal time.